2020
DOI: 10.3389/fped.2020.00467
|View full text |Cite
|
Sign up to set email alerts
|

Is Fetal Endoscopic Tracheal Occlusion (FETO) a Predisposing Factor for Acid Gastro-Esophageal Reflux in Infants With Congenital Diaphragmatic Hernia?

Abstract: Introduction: Various anatomical defects predispose patients with congenital diaphragmatic hernia (CDH) to develop gastroesophageal reflux disease (GERD). The fetal endoscopic tracheal occlusion (FETO) has increased the survival of patients with severe CDHs. The aim of this study was to study GERD in patients who underwent FETO. Materials and Methods: We included patients with CDH treated with or without FETO ("FETO" and "no-FETO" group, respectively) from 2013 to 2016. Data on gestational age (GA), birth weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A total of 858 records were identified, of which 90 were retrieved for full‐text review. Twenty‐five articles published between 2003 and 2022 were included in the qualitative synthesis 12–36 , and data from 20 articles were included in the quantitative synthesis (Figure 1) 12–14,17–19,21–25,27–30,32–36 . Among them, the four RCTs 12–14, 21 were rated as having a low risk of bias using the RoB‐2 tool, while, among the 16 cohort studies 17–19,22–25,27–30,32–36 , three were rated as having a low risk, 11 were rated as having a moderate risk and two were rated as having a serious risk of bias using the ROBINS‐I tool (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 858 records were identified, of which 90 were retrieved for full‐text review. Twenty‐five articles published between 2003 and 2022 were included in the qualitative synthesis 12–36 , and data from 20 articles were included in the quantitative synthesis (Figure 1) 12–14,17–19,21–25,27–30,32–36 . Among them, the four RCTs 12–14, 21 were rated as having a low risk of bias using the RoB‐2 tool, while, among the 16 cohort studies 17–19,22–25,27–30,32–36 , three were rated as having a low risk, 11 were rated as having a moderate risk and two were rated as having a serious risk of bias using the ROBINS‐I tool (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five articles published between 2003 and 2022 were included in the qualitative synthesis , and data from 20 articles were included in the quantitative synthesis (Figure 1) [12][13][14][17][18][19][21][22][23][24][25][27][28][29][30][32][33][34][35][36] . Among them, the four RCTs [12][13][14]21 were rated as having a low risk of bias using the RoB-2 tool, while, among the 16 cohort studies [17][18][19][22][23][24][25][27][28][29][30][32][33][34][35][36] , three were rated as having a low risk, 11 were rated as having a moderate risk and two were rated as having a serious risk of bias using the ROBINS-I tool (Table 1, Figure 2). A total of 1187 CDH patients were included in the meta-analysis, among whom 639 underwent FETO.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal endoscopic tracheal occlusion (FETO) was mentioned as a possible factor increasing the risk of GER occurrence, but retrospective multi-center studies performed by Cordier and Leva revealed that the procedure does not impact on global gastrointestinal morbidity at 2 years of age ( 56 , 57 ).…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…Recurrence of Congenital Diaphragmatic Hernia (CDH) represents a common complication in CDH survivors, along with pulmonary, gastrointestinal, neurobehavioral, and developmental anomalies (1)(2)(3)(4). It mostly happens at the site of the original hernia, but occasionally hiatal hernia may follow CDH repair due to tension on the diaphragmatic crura.…”
Section: Introductionmentioning
confidence: 99%